Analisis Kritik atas kesesuaian strategi dan eksekusi Balanced Scorecard : Implementasi Balanced Scorecard di Perusahaan Unilever - Rachman, Afifah; Geri Maulana Saputra; Hesti Kusumaningrum (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
PT Unilever Indonesia’s strategic application is examined through the Balanced Scorecard framework, focusing on four key perspectives: financial, customer, internal business processes, and learning and growth. The analysis reveals that while the company demonstrates strong financial performance, such as high ROI and ROE, challenges like declining annual profits and increasing liabilities signal the need for improved cost management and risk mitigation. Unilever's strategy emphasizes innovation and customer relationships, leveraging Total Quality Management (TQM) and continuous product enhancements. However, internal issues such as employee work culture, inadequate facilities, and employee satisfaction remain significant obstacles to organizational performance. The findings suggest a need for stronger employee engagement and workplace improvements, alongside enhanced financial sustainability strategies. Future research could explore how external factors, such as shifting market trends and government regulations, influence Unilever’s strategic decisions and overall success.